Դիտարկումներ Մածնաբերդ ամրոցի տեղորոշման հարցի շուրջ - Ալեքսանյան, Տիգրան (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Крепость Мацнаберд была одним из важных укреплений северо-восточных районов Армении. Средневековые историки неоднократно упоминали памятник без указания его местонахождения. Это обстоятельство вызвало разногласия среди исследователей. Некоторые из них (М. Оганесян, С. Бархударян, С. Карапетян) локализируют крепость за пределами Армении, на территории Азербайджана. По мнению других (Г. Алишан, А. Шахназарян, Г. Карташян, Р. Матевосян), крепость находится в регионе Тавуш Армении. The Matznaberd fortress was one of the important fortifications of the northeastern regions of Armenia. Medieval historians often mentioned the monument but without indicating its location. This circumstance has caused disagreements among researchers. Some of them (M. Hovhannisyan, S. Barkhudaryan, S. Karapetyan) localize the fortress outside Armenia, on the territory of Azerbaijan. According to others (G. Alishan, A. Shahnazaryan, G. Kartashyan, R. Matevosyan), the fortress is located in the Tavush region.
Keywords: Հնագիտություն; Տեղագրություն; Պատմություն